2021
DOI: 10.1155/2021/8838131
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Rice Flour Suspension Treated by Ultrahigh Hydrostatic Pressure

Abstract: This study investigated the physicochemical properties of rice flour suspensions under ultrahigh hydrostatic pressure (UHP) treatment. Rice flour suspensions were subjected to 200, 400, and 600 MPa of pressure for 10 min, and heat treatment was used as a control. Proximate characteristics of different rice cultivar were analyzed to amylose, damage starch content, and particle size. Changes in physicochemical properties of rice flour suspensions according to UHP treatment were analyzed to microscopic structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Similar behavior was reported by Wang et al (2022) when using HHP in rice bran protein hydrolysates. According to Park et al (2021), pretreatment with HHP damages the structure of the material, as it becomes gelatinized.…”
Section: Resultsmentioning
confidence: 99%
“…Similar behavior was reported by Wang et al (2022) when using HHP in rice bran protein hydrolysates. According to Park et al (2021), pretreatment with HHP damages the structure of the material, as it becomes gelatinized.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al. (2021) investigated the effect of HPP on starch digestibility in both flours and starches extracted from flours. It was reported that HPP treatment of rice flour at 200–600 MPa for 10 min increased the RS fraction.…”
Section: Changes In Starch Digestibility Upon Single Modificationsmentioning
confidence: 99%